SMAD4 activates Wnt signaling pathway to inhibit granulosa cell apoptosis - Du, Xing (Cell Death Dis, 2020)
The TGF-β and Wnt signaling pathways are interrelated in many cell types and tissues, and control cell functions in coordination. Here, we report that SMAD4, a downstream effector of the TGF-β signaling pathway, induces FZD4, a receptor of the Wnt signaling pathway, establishing a novel route of communication between these two pathways in granulosa cells (GCs). We found that SMAD4 is a strong inducer of FZD4, not only initiating FZD4 transcription but also activating FZD4-dependent Wnt signaling and GC apoptosis. Furthermore, we identified the direct and indirect mechanisms by which SMAD4 promotes expression of FZD4 in GCs. First, SMAD4 functions as a transcription factor to directly bind to the FZD4 promoter region to increase its transcriptional activity. Second, SMAD4 promotes production of SDNOR, a novel lncRNA that acts as a sponge for miR-29c, providing another mean to block miR-29c from degenerating FZD4 mRNA. Overall, our findings not only reveal a new channel of crosstalk between the TGF-β and Wnt signaling pathways, SMAD4–FZD4 axis, but also provide new insights into the regulatory network of GC apoptosis and follicular atresia. These RNA molecules, such as miR-29c and lnc-SDNOR, represent potential targets for treatment of reproductive diseases and improvement of female fertility.